Efficacy of collagen and alginate hydrogels for the prevention of rat chondrocyte dedifferentiation - Jin, Guang-Zhen (J Tissue Eng, 2018)
Dedifferentiation of chondrocytes remains a major problem in cartilage tissue engineering. The development of hydrogels that can preserve chondrogenic phenotype and prevent chondrocyte dedifferentiation is a meaningful strategy to solve dedifferentiation problem of chondrocytes. In the present study, three gels were prepared (alginate gel (Alg gel), type I collagen gel (Col gel), and their combination gel (Alg/Col gel)), and the in vitro efficacy of chondrocytes culture while preserving their phenotypes was investigated. While Col gel became substantially contracted with time, the cells encapsulated in Alg gel preserved the shape over the culture period of 14 days. The mechanical and cell-associated contraction behaviors of Alg/Col gel were similar to those of Alg. The cells in Alg and Alg/Col gels exhibited round morphology, whereas those in Col gel became elongated (i.e. fibroblast-like) during cultures. The cells proliferated with time in all gels with the highest proliferation being attained in Col gel. The expression of chondrogenic genes, including SOX9, type II collagen, and aggrecan, was significantly up-regulated in Alg/Col gel and Col gel, particularly in Col gel. However, the chondrocyte dedifferentiation markers, type I collagen and alkaline phosphatase (ALP), were also expressed at significant levels in Col gel, which being contrasted with the events in Alg and Alg/Col gels. The current results suggest the cells cultured in hydrogels can express chondrocyte dedifferentiation markers as well as chondrocyte markers, which draws attention to choose proper hydrogels for chondrocyte-based cartilage tissue engineering.